1990
DOI: 10.1295/polymj.22.1051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Poly(N-isopropylmethacrylamide) in Water

Abstract: Various molecular parameters characterizing solution properties of poly (N-isopropylmethacrylamide) (PNiPMAM) (in the range of moledular weight from 13.0 to 252 x 10 4) in water at 20°C were obtained by use of static and dynamic light scattering techniques. The molecular weight dependence of these parameters is expressed by the power law relation and compared with those for poly(N-isopropylacrylamide) (PNiPAM) in water. It was found that in aqueous solution PNiPMAM molecules take more expanded structures than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 20 publications
4
56
0
Order By: Relevance
“…19 The k f,0 of PNIPAM was reported to be 5.3 in water, which means that PNIPAM is a fairly flexible polymer, whose coil dimension is influenced by tacticity. 20 Previous research on the effect of tacticity on chain dimension of polypropylene showed that the statistical segment length (i.e., repeating tactic unit) of syndiotactic polypropylene is substantially higher than isotactic polypropylene. 21 Accordingly, one can rationalize these results in that PNIPAM v70 with a higher syndiotactic percentage has a higher segment length than PNIPAM v50.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 The k f,0 of PNIPAM was reported to be 5.3 in water, which means that PNIPAM is a fairly flexible polymer, whose coil dimension is influenced by tacticity. 20 Previous research on the effect of tacticity on chain dimension of polypropylene showed that the statistical segment length (i.e., repeating tactic unit) of syndiotactic polypropylene is substantially higher than isotactic polypropylene. 21 Accordingly, one can rationalize these results in that PNIPAM v70 with a higher syndiotactic percentage has a higher segment length than PNIPAM v50.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Below the transition temperature the 3 value for the VDP-PNNPAM [12.6] system was almost the same value to that for the VDP-PNIPAM [12.6] system, however, that for the VDP-PNIPMAM [12.6] system was larger than that for the VDP-PNIPAM [12.6] system. It is reported that linear PNIPMAM in aqueous solution takes a more expanded structure than linear PNIPAM due to the presence of a methyl group to the a-carbon [41]. Similarly PNIPMAM chains in the microgel particles could take more expanded structures than PNIPAM chains.…”
Section: Microenvironments Of Three Kinds Of Vdp-labeled Microgel Parmentioning
confidence: 99%
“…For instance, the solubility of poly (N-isopropylmethacrylamide͒ in water is better than the PNiPAM in water. 42 On the other hand, poly (N-n-propylacrylamide͒ is less soluble in water. 43 These facts indicate that the solution properties of PNiPAM are significantly affected by a solvation and a competition between hydrophobic and hydrophilic interactions.…”
Section: B Thermal Diffusion Of Pnipammentioning
confidence: 99%